Aspects of Lorentz violating theories of gravity - Colombo, Mattia (2016)
Lorentz symmetry is arguably the most fundamental symmetry of physics, at least in its modern conception. On the other hand, some of the issues that plague the currently accepted theory of gravitation could be solved by breaking such symmetry. The theory proposed by Petr Horava in 2009 brings forward exactly this aspect. The theory, dubbed Horava gravity, is a UV complete theory of gravity that is also renormalisable. It represents therefore a good candidate for a quantum theory of gravity.